A possible use of a polymeric surfactant as petroleum pollution collector - Rodríguez, J. L. (2007)
A polymeric amphiphile was synthesised by addition of phosphonate groups to asymmetric terminal double bonds of polybutadiene giving α, β-unsaturated phosphonic acids. The polymer was characterized by NMR and FT-IR. The synthesis produces a complex cream-like O/W emulsion containing simultaneously water and toluene. The oil droplets are interconnected by polymer chains avoiding the dispersion of the emulsion in water. When this emulsion is spread on a crude petroleum overflow on water, the oil stain shrink and is absorbed by the cream-like emulsion. The resulting product can be manipulated more easily than the original oil to extract it from the water surface.